Políticas linguísticas relacionadas à(s) escrita(s) e à(s) ortografia(s) do hunsriqueanos e as percepções dos falantes - Mühlen, Fernanda Von (Universidade do Vale do Rio dos Sinos, 2019)
This máster thesis presents a case study carried out with speakers of Hunsrückisch, a linguistic variety of German origin spoken in Brazil and with a small written tradition. The objective is to recognize the existing spelling proposals for this language in Brazil, as well as the importance (or not) of the writing of the Hunsriqueano to the speakers. It still proposes to recognize the pressures that make the speakers stop or continue using their mother tongue, as well as the pressures that are favorable to the school teaching of this variety. The instruments of the methodology were two sets of data: semi-structured interviews with fourteen speakers – half of whom did not write in this language of immigration, and the other half developed writing throughout adult life – as well as analysis of newspaper texts in books and on the internet in and about Hunsrückisch. The research results show that many speakers still do not recognize in writing a possibility the same need to use. Others, however, perceive on the internet a place where writing of this variety is feasible and useful. The speakers point out several factors that are favorable to the maintenance of the Hunsriqueano, as the language still being spoken in the family and the possibility of employment in commerce. They point out, however, that many factors exert unfavorable pressure on the language, from historical-political aspects, such as the prohibition of language during the Getúlio Vargas administration, to current elements, such as constant access to technological resources, which convey information in the language official, not on the spot. It has also been identified that school education is considered a way for the preservation of the Hunsrückisch and a possibility that the language is learned by the new generations.
Keywords: Políticas linguísticas; Hunsriqueano; Pressões; Escrita; Ortografia; Language policies; Hunsrückisch; Writting; Pressures; Orthography; ACCNPQ::Lingüística, Letras e Artes::Lingüística